Comparison of Elasticity Modulus and Nanohardness of Various Dental Restorative Materials - Gunce Ozan; Meltem Mert Eren; Zuhal Yıldırım Bılmez; Aliye Tugce Gurcan; Yasemin Yucel Yucel (Mashhad University of Medical Sciences, 2021)
Introduction: Restorative materials are under constant loadings from mastication hence, it is important to have the knowledge of structural properties of the restorative materials to have long-term success on restorations. Therefore, the aim is to compare the nanohardness and elastic modulus values of various restorative materials. Methods: Disc-shaped samples were prepared from a high viscosity glass ionomer - Equia Forte Fil (EFF), a compomer - Dyract (DXP), a hybrid ionomer - Geristore (GS), a giomer bulk-fill - Beautifil-Bulk (BB), two bulk-fill composites - Venus Bulk-fill (VB) and Sonic Fill 2 (SF), and a nanohybrid composite - Z250. Samples of each of the tested materials (n=9) were examined under nanoindentation to evaluate elasticity modulus (Er) and nanohardness (Hnano) scores. One of the samples had undergone through scanning electron microscopy (SEM) evaluation. Data were analyzed statistically using the Kruskal-Wallis test. Results: SF had the highest elasticity modulus, followed by Z250 and DXP, without any statistical differences. However, GS had the lowest elasticity modulus, followed by EFF (P<0.001). Among nanohardness scores, there is no significant difference between VB, EFF, DXP, Z250, and BB groups. While SF showed the highest, GS had the lowest nanohardness scores. SEM images showed the differences between filler sizes and shapes. Conclusion: Main structural differences between glass ionomer-based and resin-based materials determined significant differences among related parameters of the restorative materials